Psychological distance in language learning: a case study in higher education - Zumam, Wildona; Amiruddin, Mohammad (English Education:Journal of English Teaching and Research, 2023)
The purpose of this study is to describe the psychological distance between students and teachers in higher education. This is a qualitative case study. This study includes students from Madura University's English Department. The purposive sampling approach is used to choose a sample. To collect data, major sources of information include observation and interviews, with documents acting as secondary sources. The study's findings show that the psychological distance between Students and lecturers improve students' learning processes and provide input for learning. These tactics are used by teachers to maintain a psychological distance from their students. According to 13 (36.1%) of the students, encouraging youngsters to voice their thoughts, statements, and points of view is one approach for keeping their distance. Motivating students increases the psychological barrier between teachers and students. 14 (41.7%) of students agree, whereas 8 (22.2%) believe professors also say hallo or greet students. It suggests that instructors and members of academic society give students with an appropriate linguistic environment in order to provide optimum classroom settings for students to obtain relevant information as well as social interaction in order to improve students' comprehension of their society. Members of academic societies are urged to be responsive in order to provide useful feedback to students and to interact in a natural way on a regular basis.